Active offer, actors, and the health and social service system: An analytical framework - Vézina, Sylvain; Savard, Sébastien (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This chapter presents a theoretical framework inspired by strategic analysis, also called the sociology of organizations. By adopting this approach, researchers try to uncover the objectives and strategies used by the actors involved in order to better grasp the dynamics of the system of action, while at the same time taking into consideration the constraints arising from the formal structure. The concepts dealt with include the system of action, power, rules of the game, change, strategy, actor, issue, organization, and environment, all of which take into account the complexity of the challenges surrounding the practice of active offer in health and social services. One of the major contributions of this approach is that it provides an analytical framework making it possible to gain a better comprehension of the relationship between the actor and the system. These two components are essential not only for understanding the subject explored here, but also for identifying the strategies for action used by actors in a given community. Key Words: active offer, social services and health, system of action, power, zone of uncertainty, strategic analysis, sociology of organizations, change, strategy, actor, issue, organization, environment.
Chapter 1